Global randomized consensus algorithm resist collusion attack based on game theory - Bao ZHANG; Youliang TIAN; Sheng GAO (网络与信息安全学报)
As the cornerstone of blockchain technology, consensus technology has received more attention with the continuous development of blockchain technology.The development of consensus technology has become more and more rapid, but there are still related problems.Nowadays, fault-tolerant consensus algorithms, as one of the representative blockchain consensus technologies, still have many problems to be studied.The problem of node randomness and node collusion attacks in fault-tolerant consensus algorithms had been studied, and a game-theoretic-based anti-corruption algorithm was proposed.The global randomization consensus algorithm of collusion attack improved the security and throughput of the blockchain network by realizing the randomization of nodes and solving related security problems.In the process of selecting nodes participating in the fault-tolerant consensus algorithm, the global randomization of the initiator and verifier nodes was realized by using the mapping function and the weighted random function, thereby ensuring the identity anonymity of the initiator and verifier nodes and improving the blockchain network security accordingly.The reputation update model was used to realize the dynamic update of the reputation, and the game theory was used to analyze the security problems of the fault-tolerant consensus algorithm.A more correct and efficient algorithm model was constructed to improve the throughput of the algorithm and analyze the problem of collusion attack of more than one third of the nodes in this kind of algorithm, the refined Bayesian game was used to construct a collusion contract and analyze the collusion The Nash equilibrium point between the two nodes was adopted to solve the collusion attack problem of more than one third of the nodes.The security analysis and experiments show that the global randomization consensus algorithm based on the game theory anti-collusion attack is better than PoW、PoS and PBFT.The consensus algorithm is not only effective to improve throughput and reduce computing resource consumption, but also resistant to DDoS, Eclipse attacks and collusion attacks by more than one third of nodes.